Digital Nomads and International Taxation of Income from Employment - Rafał Lipniewicz (Krytyka Prawa)
With ongoing economic, social, and technological changes, the nature and method of performing work are changing. The development of modern digital technologies has a significant impact on the traditional model of work, based on performing it in a strictly defined ‘physical’ place and under an employer’s supervision. Naturally, the ongoing changes are multidimensional and have consequences, including an intriguing phenomenon of remote work, which in the cross-border dimension has led to the emergence of a new group of labour providers known as ‘digital nomads’. The specificity of business activity of these nomads poses conceptual and practical challenges in the area of various branches of law, including tax law. The main pur-pose of the article is to answer the question whether international tax law, adequately to the changes taking place, regulates the taxation of digital nomads’ income from cross-border remote work.